Morality in The Social Context - Ribakovienė, Vanzeta (Problemos, 1983)
The interrelation between morality and social changes is dealt with in the article. Two aspects of morality are singled out: (a) morality as a purely social phenomenon and (b) morality of principles. Both aspects are found to be present in any concrete historical morality. During a period of relative stability in social relations the importance of morality as a social phenomenon increases. At the break of historical epochs, how ever, the search for human “nature”, for the principles and values of man’s behaviour intensifies in the field of ethics.